Māori Girl with a Typewriter, 1906 - Wood, Peter (Architectural History Aotearoa, 2019)
This paper takes its title from a photograph held by the Alexander Turnbull Library. Recorded by Stefano Webb Photographic Studio of Christchurch, it is a studio study that falls somewhere between being a portrait, commercial illustration or candid record. The subject for the photograph - as the name reveals - is a young Māori woman sitting in front of a typewriter. Her fingertips touch the keys of the machine but her relationship to this quintessential object of the "modern" office-place is juxtaposed against surfaces that are distinctly indigenous: the woman wears a feather cloak and the typewriter is placed on another flax one. In turn this display is situated in a generic office environment. In totality the photographic is thematically and pictorially enigmatic, and we might reasonably wonder what purpose it served? In this work I conduct a comprehensive visual analysis and suggest that there may not be one main motivation behind it but a series of experiments, both conscious and unconscious to the photographer, that govern the creation and interpretation of this photograph. Central to my reading is the presence of an architectural mise-en-scene that organizes and activates the pictorial mystery, and so, while this does not depict an heroic architectural object it nonetheless depends upon an appreciation of how architecture might organise a photographic record.